Kemampuan Literasi Numerasi Siswa Di Sd Inklusi - M.M Endang Susetyawati; Kintoko Kintoko (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
Numerical literacy is a set of abilities and skills of a person in applying the concept of numbers and arithmetic operations related to everyday life. Therefore numeracy literacy plays an important role as a person's basic ability to solve everyday problems. This study aims to determine the numeracy literacy skills of students with special needs in inclusive elementary schools. The research was conducted at an Inclusion Elementary School in DIY, from January to March 2022. The method used in the research was quantitative descriptive analysis. Of the 33 test takers with 28 normal students and 5 students with special needs (Slow Learner). There are 3 students or 9% of the number of test takers, who can write down what is known from the story questions and write down what is asked. There are 6 students (18.18%) who can write formulas or mathematical sentences. There are 14 students (42.42%), who can complete the calculation correctly. There are 10 students (30.3%) students who can make conclusions.